Megaptera novaeangliae ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Megaptera novaeangliae (Borowski, 1781) —Humpback Whale Balaena novae angliae Borowski, 1781 p.21; Type locality- New England Coast, US. Balaena nodosa Bonnaterre, 1789 p.5; Type locality- New England Coast, US. Megaptera kuzira Gray, 1850 p.30; Type locality- Japan. Megaptera versabilis Cope, 1869 p.15; Type locality- North Pacific. Megaptera nodosa: Kuroda, 1938 p.12; Won, 1968 p.243. Megaptera novaeangliae: Won, 1958 p.434; Won, 1967 p.80; Kim et al, 2000 p.62; Kim, 2004 p.223. Megaptera nodosa nodosa: Won, 1968 p.244. Megaptera novaeangliae kuzira: Jackson et al., 2014 p.8 (North Pacific). Range: Humpback whales inhabit coastal waters. The first record of M. novaeangliae in Korea occurred in 1911 in the waters off Ulsan (Andrews 1916). During the Japanese invasion (1910–1945), fishermen caught 128 humpback whales in the Korean waters; since 1958, only 13 were captured (Park 1987). More recently, observations of humpback whales have regularly been made in waters southeast of Korea (Kim 2004; Fig. 80). ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 121-123, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...